Pengaruh Tingkat Perputaran Kas Terhadap Nilai Rentabilitas - Tambunan, Nurma; Wanevi, Anita; Cahya Kusumawati, Annisa; Adeliana, Dina; Luthfiatuzzahro, Hani; Rahman, Habibi; Batistuta Fauzi, Rico; Fatimah, Siti (CV. Lafadz Jaya, 2023)
Cash turnover is a measure of efficiency in the use of cash by a company. The cash turnover rate describes the speed of cash flow, the return of cash that has been invested in working capital. In measuring the level of cash turnover that has been embedded in working capital is derived from the company's operational activities. The research method used in this study is regression analysis on the financial data of companies listed on the capital market. In addition to the cash turnover rate, control variables such as company size, leverage, and sales growth are also included in the analysis to gain a more comprehensive understanding. This study aims to investigate the effect of the level of cash turnover on the profitability of a company. The level of cash turnover is considered an important indicator in measuring the efficiency of financial management, while the value of profitability reflects the profits generated by the company from the investments made. The results of this research show that there is a positive relationship between the level of cash turnover and profitability. In other words, when the cash turnover rate increases, the value of profitability also tends to increase